Bio-based carrageenan composite coatings for food packaging application - Chinchay Gallardo, Etel Huadalupe (2023)
21st LACCEI International Multi-Conference for Engineering, Education, and Technology: “Leadership in Education and Innovation in Engineering in the Framework of Global Transformations: Integration and Alliances for Integral Development”, Hybrid Event